Outcomes of neonates with congenital diaphragmatic hernias in South-East Queensland - Meghan Jones; Luke Jardine (Elsevier, 2024)
Introduction: Congenital diaphragmatic hernias (CDH) affect approximately 1 in 3000 live births (Dingeldein, 2018).1 Neonates with CDH require surgery early in their life to repair the defect in the diaphragm allowing maximal lung expansion without hinderance from abdominal organs. Due to the defect and herniation of abdominal contents, neonates can suffer associated issues including hypoxia, lung hypoplasia and persistent pulmonary hypertension (Dingeldein, 2018).1 There are established indicators of severity for CDH which include side of lesion, liver herniation, degree of lung hypoplasia, and type of treatments required (Kosiński and Wielgoś, 2017; Lee et al., 2018, Vieira et al., 2018).2-4 Method: This is a retrospective audit of neonates with CDH treated at the Mater Mothers Hospital Neonatal Intensive Care Unit. Data was collected on all neonates admitted with CDH, between 01/01/2016 and 31/12/2020. Factors associated with mortality and extracorporeal life support (ECLS) were reviewed against available international data. Results: There were 38 neonates included in the study, with a 76 % survival rate. Factors associated with mortality and ECLS were liver herniation, oxygenation index, time on conventional ventilation, and type of surgical repair. Conclusion: This information enhances our understanding of the key indicators of severity for patients with CDH. Therefore, this will allow for more well-informed future management of patients, and assist antenatal parental counselling.